Evaluation of some Winter Chickpea Varieties Under Dry Farming. - Ali, Jamil J. Mohamad; Tofiq, Sherwan I.; Ahmad, Ismael M. (Sulaimani Journal for Pure and Applied Sciences, 1997)
This study was carried out during three successive winter seasons (1991-1994), to evaluate some introduced chickpeas varieties or their yield and other agronomic traits under dry farming prevailing in Sulaimani Region. Results obtained showed that the introduced varieties tested in this investigation possess a good yield ability, survival to climatical conditions prevailing in the region and a suitable plat height which makes them convenient for mechanical harvesting, specially the varieties number 1,2,5 and 6. The combined analysis showed that the variety number 6 was ranked number 1 among the highest yielding varieties.